Hard Gelatin Capsules (Two Piece) – A Unique Pharmaceutical Dosage Form - An Exhaustive Review - Mallik, Jony; Faruq, Abdullah Al; Chowdhury, Hafsha Begum; Dinar, Md. Abu Monsur (Asian Journal of Pharmaceutical Research and Development, 2013)
Pharmaceutical dosage form are the most vulnerable house to hold the medicament(s) along with excipients. From the ancient time to today, number of different dosage form included to pharmaceutical sciences. Every dosage form has distinct character in distributing, releasing & delivery of drug(s). Hence, dosage form play a very vital role for providing therapeutic responses. Capsule is the most popular solid unit dosage form having two types -Hard gelatin and Soft gelatin capsules. Hard gelatin capsules are extensively used as for dispensing many of the active pharmaceutical principles. Specially in case of manufacturing, Hard gelatin shell is required to encapsulate the mixed materials. Most instances, company purchased the shell from supplier. The integrity, thickness, locking quality of empty shell are important for quality capsules. Recently, modified pellets incorporates within shell for upgrading pharmaceutical purposes.